2012
DOI: 10.2337/dc11-1791
|View full text |Cite
|
Sign up to set email alerts
|

Depression Predicts All-Cause Mortality

Abstract: OBJECTIVEDepression affects up to 20–25% of adults with type 2 diabetes and may increase all-cause mortality, but few well-designed studies have examined the effects of depression on the full range of cardiovascular disease outcomes in type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 2,053 participants in the ACCORD (Action to Control Cardiovascular Risk in Diabetes) Health-Related Quality of Life substudy completed the Patient Health Questionnaire (PHQ)-9 measure of depression symptoms at baseline and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 26 publications
11
84
0
4
Order By: Relevance
“…Of those we assessed, female sex, African American race or Hispanic ethnicity, low education (i.e., less than high school), being unemployed, being without health insurance coverage, low socioeconomic status, and medical illness are consistently viewed as significant risk factors (24,30), as they were shown to be in this study. For patients with type 2 diabetes, the literature shows that those who are poorer, less educated, unemployed, without insurance, and who have more complications are more likely to be depressed (6)(7)(8)(9)(10)(11)13,14). We found similar results in our sample of adults with T1D.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Of those we assessed, female sex, African American race or Hispanic ethnicity, low education (i.e., less than high school), being unemployed, being without health insurance coverage, low socioeconomic status, and medical illness are consistently viewed as significant risk factors (24,30), as they were shown to be in this study. For patients with type 2 diabetes, the literature shows that those who are poorer, less educated, unemployed, without insurance, and who have more complications are more likely to be depressed (6)(7)(8)(9)(10)(11)13,14). We found similar results in our sample of adults with T1D.…”
Section: Discussionsupporting
confidence: 84%
“…We note, however, that "other depression" is not a DSM diagnostic entity, but we use this label to capture a group with symptoms of depression that are not likely to meet DSM criteria. Sullivan et al (11) used this algorithm in the ACCORD trial and found that less than half of those defined as depressed using PHQ-9 $10 as the cutoff were defined as depressed with the algorithm.…”
Section: Depressionmentioning
confidence: 99%
“…3 Depression, an important comorbidity among adults with diabetes, has been associated with poorer disease selfmanagement and greater risk of diabetic complications, including microvascular and macrovascular disease, demen-tia, and early mortality. [4][5][6][7][8] This association is substantial in magnitude; estimates suggest that smoking, poor diet, and inactivity may be increased by 30-100 % and the risk for adverse outcomes including dementia and mortality doubles when diabetes is complicated by depression. [5][6][7] However, depression is often unrecognized among patients with diabetes in primary care settings, and adequate antidepressant treatment is received by less than one-third of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among adults with diabetes, depression is associated with impaired self-care and increased risk of microvascular and macrovascular complications, dementia, and mortality. [8][9][10][11][12] Therefore, effective treatment for depression is particularly important for people with diabetes. However, little is known about factors that influence adherence to antidepressant medications, the most common treatment for depression, in this population.…”
Section: Introductionmentioning
confidence: 99%